The Effects of ESG Disclosure, Intellectual Capital, and Environmental Costs on Firm Value: The Moderating Role of Profitability - Rizki Risdianto; Susi Susilawati; Ridwan Saleh; Samukri Samukri; Maria Suryaningsih (Journal of Enterprise and Development (JED), 2026)
Purpose: This study examines the effects of ESG disclosure, intellectual capital, and environmental costs on firm value. It also assesses the moderating role of profitability in companies listed on the Indonesia Stock Exchange.Method: This study employed a quantitative research design using panel data regression analysis. The sample was selected through purposive sampling and consisted of 90 companies during 2021-2024, resulting in 360 firm-year observations.Result: The empirical findings show that ESG disclosure, intellectual capital, environmental costs, and profitability do not significantly affect firm value. In addition, profitability does not moderate theeffects of ESG disclosure, intellectual capital, and environmental costs on firm value.Practical Implications for Economic Growth and Development: The findings indicate that the variables examined in this study do not significantly contribute to firm value. This suggests that the economic benefits of ESG disclosure, intellectual capital, environmental costs, and profitability have not been clearly reflected in market valuation. Therefore, further evaluation is needed to understand how these activities can create value that is recognized by investors.Originality/Value: This study contributes to the existing literature by examining profitability as a moderating variable in the relationships between ESG disclosure, intellectual capital, environmental costs, and firm value across several industry sectors in Indonesia.